Evaluation of the Nova Scotia Small Claims Court - Marc W. Patry, Veronica Stinson, & Steven M. Smith, Department of Psychology. (My University, 2016)
This is a final report on a research program focusing on the Nova Scotia Small Claims Court. The purpose of the present study was to examine the effectiveness of the Nova Scotia Small Claims Court at meeting its basic objective of providing quick, informal, and affordable access to justice. This research was conducted by a Saint Mary’s University research team working in collaboration with the Law Reform Commission of Nova Scotia. The data illustrate the strengths and weaknesses of the Nova Scotia Small Claims Court. The court is performing remarkably well at achieving its legislative objectives. Enforcement of judgments emerges as a clear area of concern, both among interviewees and litigants. We make several recommendations for possible reform. We recommend careful planning and  reform of data collection in the Nova Scotia Small Claims Court, with an eye toward future research.